(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The purpose of the present paper is to examine the potential obstacles to the integrity of scientific research posed by conflicts of interest. The article provides an introduction to conflict of interest as a general field of study from a multidisciplinary perspective, followed by an overview of the historical background to this issue. After reviewing the regulatory framework governing conflicts of interest in the Italian legal system, this contribution discusses the distinction between financial and non-financial interests in scientific research. In the following sections, a European and comparative perspective is provided on conflicting interests in clinical trials. In the concluding paragraphs, disclosure mechanisms and independent bodies are discussed as tools for preventing conflict of interest.